1984
DOI: 10.1128/aem.48.4.699-701.1984
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods of enumerating coliforms after UV disinfection

Abstract: In view of the differences that have been found between the most-probable-number and membrane filtration methods for the recovery of coliforms from chlorinated samples, the survival of total and fecal coliforms in UVirradiated effluent samples, as tested by the most-probable-number and standard single-step membrance filtration methods, was compared. There were no significant differences in the survival of total and fecal coliforms, as tested by the two methods. In a separate set of experiments comparing total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Samples of secondary effluent were collected from the Sandy Creek Wastewater Treatment Plant, Durham, N.C. A portion of the samples was gently filtered through a nylon screen with approximately 10-,um pores to remove most of the larger particles capable of harboring embedded bacteria. These samples were irradiated within 2 h. Coliform survivors were enumerated by the one-step total coliform membrane filtration procedure (1), since no significant difference was found for the survival of UV-irradiated coliforms as enumerated by either the standard membrane filtration or most-probable-number total and fecal coliform procedures (21). Standard plate count microorganisms were enumerated according to standard methods (1).…”
Section: Methodsmentioning
confidence: 99%
“…Samples of secondary effluent were collected from the Sandy Creek Wastewater Treatment Plant, Durham, N.C. A portion of the samples was gently filtered through a nylon screen with approximately 10-,um pores to remove most of the larger particles capable of harboring embedded bacteria. These samples were irradiated within 2 h. Coliform survivors were enumerated by the one-step total coliform membrane filtration procedure (1), since no significant difference was found for the survival of UV-irradiated coliforms as enumerated by either the standard membrane filtration or most-probable-number total and fecal coliform procedures (21). Standard plate count microorganisms were enumerated according to standard methods (1).…”
Section: Methodsmentioning
confidence: 99%
“…Research has demonstrated that the effects of water composition (turbidity, temperature, ionic strength, pH, and so forth) are probably the most significant with respect to field applications of solar disinfection. For example, an adverse effect of suspended solids on UV disinfection has been reported by several authors (Acra et al, 1990;Qualls et al, 1984;and Screible, 1987). In this case, sunlight attenuation by particulate matter was not expected to be significant because of the low turbidity levels in the contaminated water used (0.8 to 0.9 Nephelometric turbidity units).…”
Section: Resultsmentioning
confidence: 89%